Economic crises and the erosion of sustainability: A global analysis of ESG performance in 100 countries (1990–2019) - Chun Kai Leung; Jeremy Ko; Xiaoxian Chen (Innovation and Green Development)
This study investigates the relationship between national economic crises and Environmental, Social, and Governance (ESG) performance across 100 countries from 1990 to 2019. While ESG frameworks have gained prominence in assessing sustainability, limited attention has been given to the role of economic instability in shaping national ESG outcomes. By drawing on insights from geography, sociology, and development studies, this research explores how economic disruptions affect the ESG dimensions of sustainability. Using a fixed-effects regression model and multiple robustness checks, the findings indicate that economic crises are associated with significant declines in national ESG performance, with developing countries being more adversely affected than developed ones. The disaggregated analysis reveals that social and environmental dimensions are particularly vulnerable during crises, while governance performance also suffers. Among the different types of crises, sovereign debt and currency crises exert the most severe impacts, reflecting their broader structural consequences on national sustainability efforts. This study highlights the interdependence between economic stability and ESG outcomes, underscoring the need for further research into the mechanisms linking economic disruptions and sustainability metrics. The findings provide policymakers with insights for designing strategies that mitigate the adverse effects of economic crises on sustainability in an increasingly volatile global context.